2022
DOI: 10.3390/molecules27092848
|View full text |Cite
|
Sign up to set email alerts
|

Development of 1-(4-(Substituted)piperazin-1-yl)-2-((2-((4-methoxybenzyl)thio)pyrimidin-4-yl)oxy)ethanones That Target Poly (ADP-Ribose) Polymerase in Human Breast Cancer Cells

Abstract: A number of uracil amides cleave poly (ADP-ribose) polymerase and therefore novel thiouracil amide compounds were synthesized and screened for the loss of cell viability in a human-estrogen-receptor-positive breast cancer cell line. The synthesized compounds exhibited moderate to significant efficacy against human breast cancer cells, where the compound 5e IC50 value was found to be 18 μM. Thouracil amide compounds 5a and 5e inhibited the catalytical activity of PARP1, enhanced cleavage of PARP1, enhanced phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Recently, pyrimidine-based amides were developed as inhibitors of poly (ADP-ribose) polymerase, which may provide novel drug-seeds for the development of target-based drugs for BC [14]. Earlier, the synthesis of 4-fluoro-biphenyl linked 1,2,4-triazolo[1,5a]pyrimidines via click chemistry was reported and it was observed that these small molecules targeted VEGFR1 in breast cancer cells [15].…”
Section: Chemical Synthesis Of Pcls (5a-h)mentioning
confidence: 99%
“…Recently, pyrimidine-based amides were developed as inhibitors of poly (ADP-ribose) polymerase, which may provide novel drug-seeds for the development of target-based drugs for BC [14]. Earlier, the synthesis of 4-fluoro-biphenyl linked 1,2,4-triazolo[1,5a]pyrimidines via click chemistry was reported and it was observed that these small molecules targeted VEGFR1 in breast cancer cells [15].…”
Section: Chemical Synthesis Of Pcls (5a-h)mentioning
confidence: 99%
“…Heterocycles have been widely studied and integrated into medicinal chemistry due to their diverse biological activities, including targeting specific cellular pathways, DNA binding, alkylation, and apoptosis induction [4,5]. Presently, extensive research is focusing on various natural and synthetic heterocyclic compounds, such as pyrimidines [6][7][8], coumarins [9,10], pyrazoles [11][12][13], triazoles [14][15][16], oxadiazoles [17][18][19], and piperazines [20,21], among others, which have displayed promising biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Novel piperazine compounds could suppress NF-κB translocation to the nucleus [22] and inhibit NF-κB by decreasing TNF-α levels [23]. Pyrimidines also play a vital role in anti-cancer drug discovery [24]. Ibudilast, spebrutinib, and dasatinib are a few pyrimidine-based drugs (Figure 1) that block the NF-κB pathway [25].…”
Section: Introductionmentioning
confidence: 99%